Understanding PSE students’ reactions to the postplagiarism concept: a quantitative analysis - Kumar, Rahul (International journal for educational integrity, 2025)
This study examines postsecondary education (PSE) students’ perspectives on postplagiarism—a framework that reconceptualizes academic integrity in response to generative artificial intelligence (GenAI). Through a quantitative survey of 581 PSE students across five English-speaking countries, the research investigated student responses to the six tenets of postplagiarism articulated by Eaton (Int J Educ Integr 19:23, 2023a). The findings reveal a complex pattern of acceptance and resistance: while students broadly embrace the integration of GenAI in academic work, with 93.1% acknowledging the normalization of hybrid human–AI writing, significant concerns persist. Notable resistance emerged regarding the distinction between human and AI-generated content (65.92%), the potential impact of AI on human creativity (60.76%), and the retention of human agency in writing (32.7%). The study also validates a novel instrument for measuring postplagiarism perspectives, achieving acceptable internal consistency (Cronbach’s alpha = 0.718) while identifying areas for refinement. These insights suggest that educational institutions must develop nuanced policies that address student concerns while facilitating ethical AI integration, particularly in areas of attribution, creative expression, and academic agency. The findings contribute to our understanding of how academic integrity frameworks can evolve to remain relevant in an AI-integrated educational landscape.